A Tri-dimensional Equilibrium-based stochastic optimal dispatching model for a novel virtual power plant incorporating carbon Capture, Power-to-Gas and electric vehicle aggregator. (15th October 2022) - Ju, Liwei; Yin, Zhe; Lu, Xiaolong; Yang, Shenbo; Li, Peng; Rao, Rao; Tan, Zhongfu
Highlights: Design a novel structure of virtual power plant incorporated by gas-power plant carbon capture, power-to-gas and electric vehicle aggregator (C2P-VPP) Propose a tri-dimensional coordinated optimal dispatching model for C2P-VPP based on the impossibility theory of energy triangle. Construct an improved fuzzy equilibrium coordination-based-model solution algorithm for C2P-VPP considering multi-party completely rational game. Select the CIGRE medium-voltage power distribution system as the simulation system for verifying the effectiveness and applicability of the proposed. Discuss the optimal dispatching strategy of the C2P-VPP under different operation scenario. Abstract: This study proposes a novel structure of carbon-to-power-based virtual power plant (C2P-VPP) considering the flexible demand response and electric vehicle-to-grid aggregators (EVA). C2P is integrated by gas-power plant carbon capture (GPPCC), carbon storage devices (CS), and power-to-gas (P2G). Then, to balance the multiple objectives of the dispatching cost, the carbon emission and the output fluctuation, a tri-dimensional coordinated optimal dispatching model is construct from the perspective of the energy impossibility triangle problem. And the robust optimization theory is applied to characterize the uncertainty of wind power plant (WPP) and photovoltaic power generation (PV). Thirdly, to solve the above multi-objective model, an improved fuzzy equilibrium coordination-based-model solution algorithm is proposed. The algorithm integrates the fuzzy satisfaction theory, the multi-objective input income table, the entropy weight method into the complete information static game model. Finally, the CIGRE medium voltage distribution system is chosen for case study, the results show: (1) GPPCC could capture and store CO2 in carbon storage devices, and P2G could convert the CO2 into CH4 for conventional gas turbines (CGT) providing flexible power output. Compared with the scenario only with CS or P2G, when they are both introduced, the carbon emissions reduced by 7.75 % and 3.82 %, the dispatching cost reduced by 2.90 % and 7.77 %, and the output fluctuation reduced by 10.03 % and 2.80 %. (2) When robust coefficient Г is from 0.85 to 0.95, the decision-maker is the risk preference type and willing to bear risk to pursue excess benefit. (3) Sensitivity analysis shows when the rated capacity ratio of CGT, GPPCC and P2G is from 8:4:1 to 2:2:1, the dispatching scheme are optimal. When the capacity ratio of WPP, PV and EVA is from 20:1 to 10:1, the objective value changes significantly, and the optimal equilibrium scheme could be established when the capacity ratio is higher than 10:1. Therefore, the proposed optimal dispatching model could provide an effective tools for decision makers to achieve the optimal dispatching schemes.